2022
DOI: 10.1177/02601060221083079
|View full text |Cite|
|
Sign up to set email alerts
|

Low-carbohydrate diets and men's cortisol and testosterone: Systematic review and meta-analysis

Abstract: Background: Low-carbohydrate diets may have endocrine effects, although individual studies are conflicting. Therefore, a review was conducted on the effects of low- versus high-carbohydrate diets on men's testosterone and cortisol. Methods: The review was registered on PROSPERO (CRD42021255957). The inclusion criteria were: intervention study, healthy adult males, and low-carbohydrate diet: ≤35% carbohydrate. Eight databases were searched from conception to May 2021. Cochrane's risk of bias tool was used for q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“… Whittaker and Harris’ (2022) meta-analysis found that whilst low-carbohydrate diets > 3.4 g/kg/day protein decreased TT, low-carbohydrate diets < 3.4 g/kg/day protein had no consistent effect on TT. A re-examination of the relevant studies within the meta-analysis, and the wider literature, indicates that diets > 3.4 g/kg/day protein decrease TT, but diets < 3.4 g/kg/day do not; and that this effect is driven by protein intake, rather than carbohydrate or fat.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“… Whittaker and Harris’ (2022) meta-analysis found that whilst low-carbohydrate diets > 3.4 g/kg/day protein decreased TT, low-carbohydrate diets < 3.4 g/kg/day protein had no consistent effect on TT. A re-examination of the relevant studies within the meta-analysis, and the wider literature, indicates that diets > 3.4 g/kg/day protein decrease TT, but diets < 3.4 g/kg/day do not; and that this effect is driven by protein intake, rather than carbohydrate or fat.…”
Section: Discussionmentioning
confidence: 93%
“…The meta-analysis in question found that diets > 3.4 g/kg/day protein decreased TT, a finding that was based on three studies, which are listed at the top of Table 2 ( Whittaker and Harris, 2022 ). Protein intakes > 3.4 g/kg/day are above the general population's, commonly used diets, and the vast majority of athletes ( Table 1 ).…”
Section: Protein Intake and Testosteronementioning
confidence: 99%
See 1 more Smart Citation
“…Although the recommended approaches such as low-carbohydrate high-protein diet, ketogenic diet, and intermittent fasting were effective for reducing weight to get started [ 64 , 65 , 66 ], for the long term, the most effective method is still not identified because different dieting models have promoted similar weight loss [ 67 ]. Additionally, all extreme diets against obesity are hard to sustain and caution is required due to safety issues [ 68 , 69 ]. Meanwhile, overweight/obesity among college students [ 70 ] is usually overestimated as a result of following the fashion of thinness, slim food recipes, or regimens that are frequently promoted on social media [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…response to high protein low carbohydrate diets [75]. However, there is marked heterogeneity among high protein diets with variation in the types of protein, carbohydrate, and fat, as well as the presence of fibre.…”
Section: Serum Testosterone and Type 2 Diabetes Riskmentioning
confidence: 99%